2019
DOI: 10.1111/1365-2656.12941
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of heterophil/lymphocyte ratios in response to ecological and life‐history traits: A comparative analysis across the avian tree of life

Abstract: 1. Lymphocytes and heterophils are the two most abundant leucocyte types, which play a major role in adaptive and innate immune defence, respectively. The ratio of heterophils to lymphocytes (H/L ratio) may reflect a readiness to cope with infection through injury (via heterophils) rather than with a communicable disease (via lymphocytes). Since elevated H/L ratio constitutes a corticosterone-mediated response to external stressors, this trait is generally acknowledged as the robust measure of physiological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 86 publications
2
48
1
Order By: Relevance
“…There is published evidence that the heterophil:lymphocyte ratio varies between birds and is highly heritable (Campo and Davila, 2002). It also varies greatly amongst chicken breeds (Bilkova et al, 2017) and avian species (Minias, 2019). We did not observe any corresponding changes in circulating myeloid cells in these birds ( Figure 3 ) so this phenomenon appears specific to the spleen.…”
Section: Resultsmentioning
confidence: 99%
“…There is published evidence that the heterophil:lymphocyte ratio varies between birds and is highly heritable (Campo and Davila, 2002). It also varies greatly amongst chicken breeds (Bilkova et al, 2017) and avian species (Minias, 2019). We did not observe any corresponding changes in circulating myeloid cells in these birds ( Figure 3 ) so this phenomenon appears specific to the spleen.…”
Section: Resultsmentioning
confidence: 99%
“…Our second modelling exercise focused on whether lifehistory traits (maximal lifespan, maximal reproductive capacity and the interaction of both terms with body mass) explained more variation in leucocyte concentrations in birds than body mass, after accounting for phylogeny. We expected body mass to explain more variation in all three cell types than either life-history variable, but that phylogeny would also be a strong predictor as observed previously [19,[32][33][34]. We also expected the relative importance of body mass, life-history traits and phylogeny to vary among cell types because of the different defensive functions of each cell type.…”
Section: Introductionmentioning
confidence: 83%
“…The weak phylogenetic signal and a small percentage of variation in antibacterial curves explained by phylogeny in general were surprising. Previous analyses of scaling of leucocyte concentrations and in mammals (Downs et al 2020) and birds (Ruhs et al 2020) and leucocyte ratios in birds (Minias 2019) demonstrated that phylogeny explained the majority of interspecific variation.…”
Section: Phylogenetic Signal and Other Influences On Antibacterial Capacitymentioning
confidence: 99%